Pendampingan Nagari Sungai Nyalo Sebagai Nagari Yang Mandiri Berbasis CHSE Melalui Pengelolaan Digital Marketing - Sulkaisi, Neffi; Putri, Yosi Eka; Nurdin, Bernediv; Irwan, Irwan; Rosya, Nilma Desri (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2023)
The natural tourist attraction managed by Nagari Sungai Nyalo Mudiak Aia is qualified, it's just that in terms of management, the available infrastructure facilities are still lacking. The purpose of the service is to solve partner problems by assisting with skills in using digital marketing and it is needed in business development - establishing relationships, marketing, promotion, also in developing and empowering personal branding/self empowering. The implementation of PKM Digital Marketing will be carried out by Marketing Management and Digital Skill experts by Lecturers of the Entrepreneurship Study Program, Economic Education, Informatics Education and Environmental Sciences, PGRI University, West Sumatra and assisted by 3 students who already understand the concept of entrepreneurship and digital. The technology that will be applied to Sungai Nyalo MSME actors is digital-based marketing. Starting from the awareness of business actors and the availability of human resources. Then proceed with the development of social media and tourism management websites. For example, the introduction of tourist attractions through posting videos or posting photos accompanied by interesting captions that are shared on social media